Algal bioactive compounds in the cosmeceutical industry: a review. Issue 4 (1st July 2017) - Jahan, Afroz; Ahmad, Iffat Zareen; Fatima, Nida; Ansari, Vaseem A.; Akhtar, Juber
Abstract: The term cosmeceutical is derived from a combination of 'cosmetic' and 'pharmaceutical', and indicates that active ingredients are present in a specific cosmetic product. These cosmeceuticals or cosmetic products have ingredients with medical or drug-like benefits. They are formulated to increase positive physiological effects at the cellular level in addition to enhancing the skin's appearance. Cosmeceutical applications using algae are rapidly growing because of increasing demands from customers. The basic premise is that novel bioactive substances from natural sources are safer and equally or more efficacious than artificial substances. These compounds should have highly effective and stable properties for therapeutic use with low potential toxicity. Recently, marine organisms have been demonstrated as rich sources of structurally diverse, biologically active compounds with extensive cosmeceutical potential. Numerous compounds have been isolated from marine organisms, and these compounds have various purported cosmeceutical activities including antioxidant, anti-inflammatory, antiallergenic, antiaging and antiwrinkling effects, and ultraviolet protection. This review is focused on algal natural products and their potential for development of cosmeceuticals from novel and potent phytochemical compounds.